Treatment Response Appraisal in Non-Small Cell Lung Cancer Using 18F-FDG PET-CT Imaging: Insights from Initial Application of PERCIST 1.0 and RECIST 1.1 Criteria (Bangladesh Journal of Nuclear Medicine, 2026)
Introduction: An 18F-FDG PET-CT scan is increasingly used in the evaluation of treatment response for patients with non-small cell lung cancer (NSCLC) in a conventional way using SUVmax and a total body survey. The aim of this study was to evaluate responses in NSCLC patients by using PERCIST 1.0 and RECIST 1.1. Patients and methods: Retrospective data analysis of five patients with NSCLC over a 1.5-year period was done. The assessment included baseline and therapeutic response measurements using 18F-FDG PET-CTimaging at National Institute of Nuclear Medicine & Allied Sciences (NINMAS) after treatment completion, independent of the type of medication administered. Results: Three patients were male and two were female, with the mean age being 57 yrs ± 14.76 yrs (mean ± SD). All of them were diagnosed at advanced stages of NSCLC. The mean duration of response evaluation after finishing therapy was 76.6 days. Four out of five patients showed stable disease (SD) after RECIST 1.1, and one showed a complete response (CR). PERCIST 1.0 evaluation showed progressive metabolic disease (PMD) in two patients and partial metabolic response (PMR) in two patients. The patient with CR on RECIST was also found to have a complete metabolic response (CMR) on PERCIST. Conclusion: Utilizing PERCIST 1.0 and RECIST 1.1 with hybrid imaging allows for a non-invasive assessment of metabolic and morphologic responses, providing clinicians with enhanced information for managing advanced NSCLC patients.Bangladesh J. Nuclear Med. 29(1): 50-57, 2026